2023
DOI: 10.3390/nu15071611
|View full text |Cite
|
Sign up to set email alerts
|

Dried Fruits: Bioactives, Effects on Gut Microbiota, and Possible Health Benefits—An Update

Abstract: Dried fruits contain many bioactive compounds broadly classified as phytochemicals including phenolics, flavonoids, carotenoids, proanthocyanidins, stilbenes, chalcones/dihydrochalcones, and phytoestrogens. These compounds have antioxidant effects that may benefit health. Dried fruits are also a diverse group of foods with varying fibre contents. The evaluation of the biological activity of these bioactive compounds, including their bioaccessibility and bioavailability, may contribute to the understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…These natural antioxidants can alleviate oxidative stress and chondrocyte damage and thus play a role in the management of OA. [26] Ellagic acid (EA) is a natural polyphenol extracted from fruits or nuts, which can effectively inhibit oxidative stress induced by IL-1 and improve chondrocyte oxidative stress-induced dysfunction; significantly inhibit apoptosis and aging, and reduce the expression of pro-inflammatory factors and metalloproteinases; and through up-regulating Keap1/ Nrf2 signaling pathway, weaken oxidative stress and play a protective effect on chondrocytes. [27,28] Limonin reduces IL-1 levels of β-induced pro-inflammatory cytokines and reduces the biosynthesis of IL-1β-stimulated chondrogenic catabolic enzymes in chondrocytes to reduce inflammation, and exerts a protective effect on OA through the Nrf2/HO-1/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These natural antioxidants can alleviate oxidative stress and chondrocyte damage and thus play a role in the management of OA. [26] Ellagic acid (EA) is a natural polyphenol extracted from fruits or nuts, which can effectively inhibit oxidative stress induced by IL-1 and improve chondrocyte oxidative stress-induced dysfunction; significantly inhibit apoptosis and aging, and reduce the expression of pro-inflammatory factors and metalloproteinases; and through up-regulating Keap1/ Nrf2 signaling pathway, weaken oxidative stress and play a protective effect on chondrocytes. [27,28] Limonin reduces IL-1 levels of β-induced pro-inflammatory cytokines and reduces the biosynthesis of IL-1β-stimulated chondrogenic catabolic enzymes in chondrocytes to reduce inflammation, and exerts a protective effect on OA through the Nrf2/HO-1/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarettin et al considered dried fruit (raisins, cranberries, jujube, and dried plum) to affect the composition of human intestinal flora in a potentially beneficial way (in terms of bifidobacterium, Clostria, Lactobacillus, Ruminoccaceae, Klebsiella, Prevotella), thus health benefits. [26] The study showed that the pain of rat or human OA and inflammation and symptoms were reduced by administering probiotics, prebiotics, or drugs. These results suggest that dried fruit may affect the occurrence and progression of OA by affecting intestinal flora and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Dried fruits serve as nutrient-rich snacks, brimming with dietary ber, essential minerals, vitamins, and bioactive elements like avonoids and carotenoids. They offer notable health bene ts such as antioxidant, anti-in ammatory, anti-atherosclerotic, and anticancer properties [32][33][34][35]. These concentrated nutrients in dried fruits can play a signi cant role in combating oxidative stress and in ammation, two key factors in the development and exacerbation of various health conditions, including intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Butyric acid produced by the butyric-acid-producing bacteria Clostridium butyricum and Faecalibacterium prausnitzii induces regulatory T cells (Treg) in the gut, and IL-10 produced by Tregs helps suppress inflammatory responses and upregulate immunity [133]. Furthermore, flavonoid phytochemicals work as prebiotics and upregulate immunity by increasing beneficial microbiota such as butyric-acid-producing bacteria [117] and suppress chronic inflammation through lowering the production of TNF-α [118]. In addition, it is intriguing that the consumption of raisins is reported to induce beneficial changes in gut microbiota [119].…”
Section: Intestinal Disorders and Gut Microbiotamentioning
confidence: 99%